2016
DOI: 10.1152/ajplung.00047.2016
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in neonatal hyperoxic lung injury

Abstract: Male sex is considered an independent predictor for the development of bronchopulmonary dysplasia (BPD) after adjusting for other confounders. BPD is characterized by an arrest in lung development with marked impairment of alveolar septation and vascular development. The reasons underlying sexually dimorphic outcomes in premature neonates are not known. In this investigation, we tested the hypothesis that male neonatal mice will be more susceptible to hyperoxic lung injury and will display larger arrest in lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
106
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(121 citation statements)
references
References 82 publications
13
106
2
Order By: Relevance
“…Blockade of prolyl hydroxylase stabilizes HIF, and leads to increases in VEGF, PEC AM-1 levels and angiogenesis in human microvascular endothelial cells exposed to hyperoxia (Asikainen et al, 2005). In our study, HIF-1α mRNA levels were increased in female neonatal mice exposed to hyperoxia at PND7 and were decreased in male mice at PND21 which was consistent with our previous findings of decreased lung vascular development in male mice at the same time point (Lingappan et al, 2016). HIF-1α was also decreased upon exposure to hyperoxia under in vitro conditions (Figures 2 and 4).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Blockade of prolyl hydroxylase stabilizes HIF, and leads to increases in VEGF, PEC AM-1 levels and angiogenesis in human microvascular endothelial cells exposed to hyperoxia (Asikainen et al, 2005). In our study, HIF-1α mRNA levels were increased in female neonatal mice exposed to hyperoxia at PND7 and were decreased in male mice at PND21 which was consistent with our previous findings of decreased lung vascular development in male mice at the same time point (Lingappan et al, 2016). HIF-1α was also decreased upon exposure to hyperoxia under in vitro conditions (Figures 2 and 4).…”
Section: Discussionsupporting
confidence: 93%
“…The sex in neonatal mouse pups was determined by both the anogenital distance and pigmentation in the anogenital region method (Wolterink-Donselaar et al, 2009). In younger mice, the sex was reconfirmed with PCR analysis for the Sry gene in genomic DNA obtained from mouse-tail clips as described before (Lingappan et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from our laboratory and those of other investigators have shown sex-specific modulation of NF-κB pathway [79]. In a model of neonatal hyperoxic lung injury, we showed that there was a greater arrest in lung development (alveolarization and angiogenesis) in male mice.…”
Section: Introductionsupporting
confidence: 62%
“…Interestingly, female mice showed increased activation of the NF-κB pathway in the lungs compared to males. The larger decrease in angiogenesis in males exposed to hyperoxia may have been in part due to decreased NF-κB activation [9]…”
Section: Introductionmentioning
confidence: 99%